"And now we resist": Three testimonios on the importance of decoloniality within psychology. (22nd May 2021) - Silva, Janelle M.; Fernández, Jesica Siham; Nguyen, Angela
Abstract: In recent years, the field of psychology has turned to decoloniality as a potential epistemological standpoint and framework to understand how systems of power reproduce oppression (Fanon, 1963; Fernández, 2018; Maldonado‐Torres, 2016; Quijano, 2000). In classroom and community‐engaged research settings, critical community psychologists, specifically those grounded in a decolonial feminist epistemology (Bell, 2018; Dutta, 2018; Fernandez, 2018; Silva & the Students for Diversity Now, 2018), use this standpoint to analyze how they can co‐create opportunities for decolonial justice. Using testimonios as decolonial method, we reflect on how we resist colonialism within our work, specifically our teaching, research, and practice. Drawing on our lived experiences, which have been rendered unwanted subjects within the field, our testimonios are an example of how we individually and relationally engage decoloniality and decolonization as both praxis and pedagogy. Combined, we illustrate how relational reflective narratives through testimonio can illuminate the field's commitment to decolonial liberation and the dismantling of oppressive systems.